1990
DOI: 10.3347/kjp.1990.28.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Purification of antigenic protein of sparganum by immunoaffinity chromatography using a monoclonal antibody

Abstract: The quality improvement of antigen (crude saline extract) of Spirometra mansoni pleroceroid (sparganum) was investigated by protein purification. The crude extract was fractionated by gel filtration through Sephacryl S-300 Superfine. Its third fraction was purified by affinity chromatography using a monoclonal antibody as ligand. When observed by SDS-PAGE, the purified protein was composed of 2 bands of 36 kDa and 29 kDa which were found already as the most sensitive components in the crude extract by immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…[1][2][3][4] Humans are an intermediate host for the parasite and infection occurs in several ways including (a) drinking water containing infected copepods, which are small crustaceans, (b) eating amphibian, reptile or rodent meat and (c) using those meats as a poultice; a traditional self-treatment according to ritual belief. 1,4,28 These risk behaviours were identified in 41.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Humans are an intermediate host for the parasite and infection occurs in several ways including (a) drinking water containing infected copepods, which are small crustaceans, (b) eating amphibian, reptile or rodent meat and (c) using those meats as a poultice; a traditional self-treatment according to ritual belief. 1,4,28 These risk behaviours were identified in 41.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…1 In these cases the metacestode stage, normally known as a plerocercoid, is called a sparganum, and the resulting infection is sparganosis. [1][2][3][4] Sparganosis is a zoonosis contracted from amphibians, reptiles or mammals, which occurs occasionally in humans. 1,2,4 The infection is reported in many countries but is most common in eastern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme linked immuno sorbent assay (ELISA) is a sensitive and specific serodiagnostic tool for subcutaneous or cerebral sparganosis (Cho et al, 1990;Morakote & Kong, 1993), therefore it is almost possible to determine whether a patient is infected or not. It is imperative to examine inhabitants at the infection prevalent area before the worm migrates to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…; Nishiyama et al 1994). The specificity of the ELISA was partially improved when the antigens purified from the crude extract by affinity chromatography was used; but the purifying procedure is complicated and inefficient, and the cross-reactions still occur (Cho et al 1990;Kong et al 1991). Our results indicated that ES antigen ELISA is superior to crude antigen ELISA for serodiagnosis of sparganosis.…”
Section: Discussionmentioning
confidence: 62%